2013
DOI: 10.1002/ijc.28047
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical relevance of MET and ALK in Ewing sarcomas

Abstract: Because novel therapeutic options are limited in Ewing sarcomas (ES), we investigated the expression, genetic aberrations and clinical relevance of MET and anaplastic lymphoma kinase (ALK) in ES and determined the relevance of targeting these receptors. MET and ALK protein expression was determined immunohistochemically in 31 (50 samples) and 36 (59 samples) ES patients, respectively. Samples included primary tumors, postchemotherapy resections, metastases and relapses. MET and ALK RTK domains were sequenced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…Targeting c-MET is recognized as a promising opportunity for treatment of human cancers (38,39). Crizotinib is a c-MET/ALK inhibitor, which has previously been shown to have modest antineoplastic effect against EWS cells in vitro (40). In agreement with the prior study, we found crizotinib had a similar inhibitory effect on EWS cell lines, with an IC 50 about 2 mmol/L (Supplementary Fig.…”
Section: Inhibition Of Crm1 Induced Cytotoxicity By Repressing Ews-flsupporting
confidence: 90%
“…Targeting c-MET is recognized as a promising opportunity for treatment of human cancers (38,39). Crizotinib is a c-MET/ALK inhibitor, which has previously been shown to have modest antineoplastic effect against EWS cells in vitro (40). In agreement with the prior study, we found crizotinib had a similar inhibitory effect on EWS cell lines, with an IC 50 about 2 mmol/L (Supplementary Fig.…”
Section: Inhibition Of Crm1 Induced Cytotoxicity By Repressing Ews-flsupporting
confidence: 90%
“…FISH was performed on 2-mm-thick formalin-fixed paraffin embedded (FFPE) tissue microarray (TMA) sections from the patient cohort described above, and an Aska-SS cytospin using an ALK (2p23) split-signal FISH DNA probe (Dako) as described previously (21).…”
Section: Fishmentioning
confidence: 99%
“…RT-PCR and sequence analysis of the RTK domain of ALK and MET was performed on SS cell lines as described previously (21). SS cells were additionally screened with the Cancer Hotspot Panel with a focus on potential PDGFRa and EGFR mutations (23).…”
Section: Mutation Analysismentioning
confidence: 99%
“…Overexpression and aberrantly activated MET triggers cell growth, angiogenesis, invasion, and metastasis correlated with poor prognosis in various sarcomas 43, 44 . Targeting MET using the small molecule kinase inhibitor PHA-665752 and the neutralizing anti-HGF antibody sensitized osteosarcoma cells to cisplatin through suppression of the PI3K/AKT signaling 45 .…”
Section: Targeting Receptor Tyrosine Kinases (Rtks)mentioning
confidence: 99%